2021
DOI: 10.1371/journal.pone.0251846
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices regarding neonatal jaundice among caregivers in a tertiary health facility in Ghana

Abstract: Background Neonatal jaundice is a major reason babies are frequently re-admitted after hospital discharge following delivery. One means of improving neonatal care and reducing potential mortality associated with neonatal jaundice in resource-limited settings is to create awareness among caregivers. Caregivers who tend to have higher knowledge and awareness, also have positive attitudes, and are not guided by outmoded socio-cultural beliefs and practices are more likely to seek early care and treatment for neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 25 publications
3
28
1
Order By: Relevance
“…Poor knowledge about the causes and danger signs of jaundice may mean mothers turn to traditional treatments, which results in delays in seeking medical attention for neonatal jaundice, thereby contributing to the development of ABE and kernicterus. 11 Therefore, it is recommended that medical staff incorporate information about the causes and danger signs of jaundice into neonatal jaundice health education programmes. For breast milk jaundice, this involves monitoring the jaundice without changing in the infant’s breast feeding; 27 however, 73% of mothers in this study did not know that breast milk jaundice is generally a benign condition, where interruption of breast feeding is not recommended as a therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor knowledge about the causes and danger signs of jaundice may mean mothers turn to traditional treatments, which results in delays in seeking medical attention for neonatal jaundice, thereby contributing to the development of ABE and kernicterus. 11 Therefore, it is recommended that medical staff incorporate information about the causes and danger signs of jaundice into neonatal jaundice health education programmes. For breast milk jaundice, this involves monitoring the jaundice without changing in the infant’s breast feeding; 27 however, 73% of mothers in this study did not know that breast milk jaundice is generally a benign condition, where interruption of breast feeding is not recommended as a therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few mothers provided correct answers to some items; for example, ‘cranial haematoma may cause neonatal jaundice’ (29%), ‘blood test is the gold standard for diagnosing neonatal jaundice’ (34.2%), ‘it is abnormal for jaundice to appear within 24 hours after birth’ (36.2%) and ‘it is abnormal for jaundice to reappear after it subsides’ (37%). Poor knowledge about the causes and danger signs of jaundice may mean mothers turn to traditional treatments, which results in delays in seeking medical attention for neonatal jaundice, thereby contributing to the development of ABE and kernicterus 11. Therefore, it is recommended that medical staff incorporate information about the causes and danger signs of jaundice into neonatal jaundice health education programmes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased concentration of indirect bilirubin leads to acute and chronic bilirubin encephalopathy or kernicterus which results in permanent brain damage and death. Cerebral palsy, mental retardation, and hearing impairment could be consequences if jaundice is not noticed and managed early (Salia et al, 2021). However, early detection, rapid and suitable management of neonatal jaundice can be achieved by raising the level of awareness among the parents which will improve the outcome of the disease (Amegan-Aho et…”
Section: Introductionmentioning
confidence: 99%
“…Medical Science, 26, ms317e2388 (2022)NeonatalIn Ghana, 8.9% of the caregivers had good knowledge about neonatal jaundice(Salia et al, 2021). Another study in Ghana found that merely 17.3% of moms caught about newborn jaundice(Adoba et al, 2018).…”
mentioning
confidence: 99%